2007
DOI: 10.1166/jnn.2007.514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pore Size of Self-Organized Honeycomb-Patterned Polymer Films on Spreading, Focal Adhesion, Proliferation, and Function of Endothelial Cells

Abstract: The design of nano- and microstructures based on self-organization is a key area of research in the search for new materials, and it has a variety of potential applications in tissue engineering scaffolds. We have reported a honeycomb-patterned polymer film (honeycomb film) with highly regular pores that is formed by self-organization. This study describes the behavior of vascular endothelial cells (ECs) on honeycomb films with four different pore sizes (5, 9, 12, and 16 microm) as well as on a flat film. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 0 publications
6
73
0
1
Order By: Relevance
“…This allowed the effect of the pattern size of the scaffold, and no other factors, on cell functions to be investigated. The mean area of cells grown on triangles with 3 µm long sides was smaller than 8 that of cells grown on triangles with 4-15 µm long sides (Fig. 2I).…”
Section: Fabrication Of 3d Scaffolds With Different Pattern Sizesmentioning
confidence: 85%
See 1 more Smart Citation
“…This allowed the effect of the pattern size of the scaffold, and no other factors, on cell functions to be investigated. The mean area of cells grown on triangles with 3 µm long sides was smaller than 8 that of cells grown on triangles with 4-15 µm long sides (Fig. 2I).…”
Section: Fabrication Of 3d Scaffolds With Different Pattern Sizesmentioning
confidence: 85%
“…In cells cultured on 3D patterned scaffolds, the expression levels of adhesion signalling complexes, 43 focal adhesion kinase 13,43 and F-actin, 13,15,44 their proliferative, 8,13,20,22 cell aggregation [17][18][19][20] and metabolic 13,[19][20][21] capacities, and their differentiation potential, 9, 23 differ from those of cells cultured on flat surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] As reported, the elongated cells not only had increased proliferation and extracellular matrix production, but also had higher migrations speeds as compared to their spread out counterparts. [14,17,35] Since migration into wound site was a major mode re-endothelialization, enhanced EC motility might greatly promote healing after device implantation. Therefore, the proliferation and migration of HUVECs were further determined.…”
Section: Resultsmentioning
confidence: 99%
“…The results on cell retention percentage indicated that upon exposure to physiologically relevant shear stress the endothelium maintained cell population on the gel/NMCS-PLA, whilst failed on unmodified PLA, resulting a 1.6 times higher cell number on the gel/NMCS-PLA surface upon perfusion at 5 dyn cm À2 over 24 h. Endothelium endures high vascular shear stresses through cytoskeleton and ECM remodeling that allows strong adhesions between the cell and homing molecules [42]. We attributed the prevention of cell loss on the surface-modified samples to their higher cell-material interaction, and more completed endothelium composed of higher intercellular adhesion molecular amount compared to their unmodified counterparts.…”
Section: Endothelium Functionmentioning
confidence: 98%